PATHOTYPES AND VIRULENCE MARKERS IN ESCHERICHIA COLI ASSOCIATED WITH DIARRHOEA AMONG HIV SEROPOSITIVE AND SERONEGATIVE CHILDREN BELOW FIVE YEARS IN WESTERN KENYA - Salinah J Rono; Rose Kakai; Fabian Esamai; Erick Mibei; Elizabeth Odundo (European Scientific Journal, ESJ, 2014)
Diarrhoea is among the leading causes of childhood morbidity and mortality worldwide. Diarrheagenic Escherichia coli (DEC) are responsible for 30% to 40% of acute diarrhea and chronic episodes in children in developing countries. This study sought to elucidate genotypic diversity and virulence markers of Diarrheagenic Escherichia coli associated with diarrhoea among HIV seropositive and seronegative children aged below five in Western Kenya. A total of 105 diarrheagenic E coli isolates obtained from children aged below five years with diarrhoea admitted at Moi Teaching and Referral Hospital , Kenya, were subjected to multiplex PCR using seven sets of primers. The study revealed that 36 (34.2%) pathotypes were identified as; EHEC 4 (11.1%), ETEC 2 (5.6%), EAEC 21 (58.3%), EIEC 3 (8.3%) and EPEC 6 (16.7%), EAEC. Seven virulence genes were identified including EHEC shigatoxin genes, stx1 (0 vs 100%) and stx2 (0 vs 100%), ETEC heat labile, elt (0 vs 100%), and heat stable toxin, est (0 vs 100%), EPEC, bfp (33.3% vs 66.7%), EAEC, aatA (71.4% vs 28.6%) and EIEC ipaH (66.7% vs 33.3%) among isolates from HIV seropositive and negative cases respectively. EPEC and ETEC were significantly associated with acute diarrhoea episodes in HIV negative cases while EAEC was predominantly linked to persistent diarrhoea with higher incidence in HIV seropositive than seronegative cases, (p<0.05). There was a significant difference in the expression of virulence genes in relation to age.